Rocks and minerals : get the dirt on geology - Eboch, Chris (Inquire and investigate., 2020)
Explores the role of rocks and minerals in the field of geology, discussing plate tectonics, volcanoes, earthquakes, erosion, groundwater, and energy. Includes a timeline, a glossary, color illustrations, discussion questions, STEM activities, and fact boxes.